Life Cycle Assessment of electricity generation from Jatropha oil in a short chain in Mali - Leticia MENEGHEL FONSECA; Nawelle CHAOUKI; Anthony BENOIST; Guillaume BUSSET; Roland PIROT; Mireille MONTRÉJAUD-VIGNOLES; Caroline SABLAYROLLES (Indonesian Journal of Life Cycle Assessment and Sustainability, 2019)
Jatropha curcas is an inedible oil crop which can grow under semiarid climatic conditions. Its oil can be used straight as fuel to provide energy in remote areas to improve living conditions. The aim of this study is to assess the environmental impacts of the electricity generation from Jatropha oil under West African conditions, by means of a Life Cycle Assessment (LCA). These potential impacts are calculated for four crop managements and compared to the ones of a reference electricity generation from conventional diesel. Data used in this work are from Jatropha plantations set up in Mali since 2006.LCA results show that the potential benefits of the Jatropha systems are highly dependent on the crop management, especially for the fertilization strategy and the promotion of the oilcake. However, in all cases, the Jatropha systems have lower impacts than the reference diesel system by 75% to 96% for abiotic depletion, and by 80% to 97% for ozone layer depletion, and higher impacts by 260% to 1000% for eutrophication, and by 26% to 160% for acidification. In the best case, the Jatropha system can also have lower impacts than the reference system by 76% for climate change, and by 88% for photochemical oxidation.A methodological originality of this work is the inclusion of animal and human labour into the LCA framework. A first model is proposed for the accounting of energy consumption and GreenHouse Gases (GHG) emissions due to labour. Concerning energy consumption, labour is not negligible with a share from 14% to 50% of the total impact of the Jatropha systems; however the highest share of 50% corresponds to the scenarios with the lowest energy demand. CH4 emissions from livestock are also not negligible but second-order in this study since they account for 2% to 13% of total GHG emissions.